Flow Cytometry Identifies a Spectrum of Maturation in Myeloid Neoplasms Having Plasmacytoid Dendritic Cell Differentiation. Issue 1 (5th January 2019) - Hamadeh, Fatima; Awadallah, Amad; Meyerson, Howard J.; Beck, Rose C.
Abstract : Background: Neoplasms derived from plasmacytoid dendritic cells (PDCs) are currently divided into two broad categories: mature PDC proliferations associated with myeloid neoplasms (MPDMN) and blastic plasmacytoid dendritic cell neoplasm (BPDCN); only BPDCN is recognized in the WHO 2016 classification of hematopoietic neoplasms. We present seven patients with high grade myeloid neoplasms (MNs), mostly acute leukemias, having a spectrum of PDC differentiation and not fitting with MPDMN or BPDCN. Methods: We analyzed seven MN cases having increased myeloblasts and prominent CD56‐negative PDC proliferations comprising 5–26% of bone marrow or blood cellularity as measured by flow cytometry. The cases included five acute myeloid leukemia (three FAB M4 subtype, two unclassified), one mixed phenotype acute leukemia, and one case of unclassified MN. Results: Six cases demonstrated immunophenotypic evidence of PDC differentiation from leukemic blasts, based on variable expression of CD34, CD45, CD123, and CD304 by the leukemic cells. Four cases had circulating PDC populations in blood. None of the cases met clinical or pathologic criteria for BPDCN. Morphologic review was available for four acute leukemia cases and demonstrated either nodular or interstitial infiltrates of PDCs. All cases had an aggressive clinical course, and three cases had FLT3 ITD mutation. Conclusions: These cases demonstrate that high grade MNs, in particular AML, can exhibit PDC differentiation, with or without monocytic differentiation, in a manner distinct from MPDMN or BPDCN. The existence of MNs with immature PDC proliferations suggests that there is a broader spectrum of PDC‐associated neoplasms than currently recognized. © 2019 International Clinical Cytometry Society